Evaluation of Techniques for the Improvement of Subgrade Soils in Flood and Rainfall Inundation Affected Areas: Improvement of Subgrade Soils in Flood and Rainfall Inundation Affected Areas - Khan, Ammad Hassan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
Highways are amongst the most costly resources contributing directly to the growth of any country’s economy. Subgrade soils as component of highways deteriorate normally from numerous factors resulting into flushing or excessive settlements of embankment involving huge maintenance costs. In this research, an attempt has been made to evaluate suitable technique for stabilization of commonly available subgrade soils of Pakistan based on cost effectiveness and ease in construction. The soils identified as A-3(0) by American Association of State Highway and Transportation Officials (AASHTO) criteria has been stabilized with conventional additives i.e. cement and bitumen in this research. The optimum content of each additive for stabilization based on their relative effectiveness was used. Trials were also made to economize the cost of stabilization from both conventional additives by controlled replacing of them with waste polythene and polyester fibers. The construction methodology for stabilization using waste fibers was also proposed. Cement was observed to be the most effective stabilizer with respect to strength and durability for A-3(0) soils. Bitumen was found effective but uneconomical for A-3(0) soils. Waste polythene and polyester wastes (organic materials) have potential to economize the cost of stabilization with cement and bitumen for A-3(0) soils. However, long term degradation of these organic materials in soil stabilized mixtures needs further exploration.